2021
DOI: 10.1128/mbio.00860-21
|View full text |Cite
|
Sign up to set email alerts
|

O-Specific Antigen-Dependent Surface Hydrophobicity Mediates Aggregate Assembly Type in Pseudomonas aeruginosa

Abstract: During chronic infection, several factors contribute to the biogeography of microbial communities. Heterogeneous populations of Pseudomonas aeruginosa form aggregates in cystic fibrosis airways; however, the impact of this population heterogeneity on spatial organization and aggregate assembly is not well understood.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 70 publications
(107 reference statements)
2
26
0
Order By: Relevance
“…The results suggest that reducing the production of cell-surface-associated lipopolysaccharides and exopolysaccharides can increase the hydrophobicity of the cell surface (i.e., the interfacial energy among oil, water, and cell surfaces), which can help the cells to be trapped at the oil–water interface. This agrees with the result of an earlier study where Δ wbpL was shown to have an increased relative cell surface hydrophobicity . Based on a similar mechanism, a Staphylococcus sp.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The results suggest that reducing the production of cell-surface-associated lipopolysaccharides and exopolysaccharides can increase the hydrophobicity of the cell surface (i.e., the interfacial energy among oil, water, and cell surfaces), which can help the cells to be trapped at the oil–water interface. This agrees with the result of an earlier study where Δ wbpL was shown to have an increased relative cell surface hydrophobicity . Based on a similar mechanism, a Staphylococcus sp.…”
Section: Resultssupporting
confidence: 91%
“…We cultured gentamicin-resistant colonies in LB broth devoid of NaCl (LBNS) without antibiotics and plated the colonies on LBNS agar plates containing 10% sucrose. We then selected sucrose-resistant colonies, screened them for gentamicin sensitivity to ensure the loss of the PEX18GM construct, and assessed them for the desired gene deletion by colony PCR and Sanger sequencing of the PCR product …”
Section: Methodsmentioning
confidence: 99%
“…Clinical isolates with different biological characteristics could affect depletion-mediated bacteria-bacteria interactions. For example, recent work demonstrates that LPS O-antigen modifications in P. aeruginosa change cell surface hydrophobicity, which may disrupt the tightly-packed and ordered cell arrangements characteristic of depletion aggregates ( Azimi et al., 2021 ). Other surface modifications that affect surface charge could also affect depletion-mediated bacteria-bacteria or bacteria-polymer interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The second step of biofilm establishment i.e., the micro-colony formation is characterized by bacterial adhesion, aggregation and persistence; each of these phenomena are dependent on cell surface hydrophobicity (CSH). Generally, P. aeruginosa exhibits hydrophobic cell surface, which is correlated with slow growth, strong biofilm formation and persistence (49); clinical isolates of mucoid, slime-producing strains of P. aeruginosa become non-adherent by alteration of CSH, while non-mucoid, non-slime producing strain become adherent with high affinity by increasing CSH (50). Eugenol is shown to inhibit biofilm formation and adhesion on Hep-2 (human larynx epidermoid carcinoma) cell line and on polystyrene by decreasing of CSH in Candida dubiliniensis and C. tropicalis (51).…”
Section: Discussionmentioning
confidence: 99%